2017
DOI: 10.3856/vol45-issue1-fulltext-25
|View full text |Cite
|
Sign up to set email alerts
|

Deep ventilation event during fall and winter 2015 in the Puyuhuapi Fjord (44.6 S)

Abstract: ABSTRACT. The Puyuhuapi Fjord has previously been reported as one of the hypoxic fjords in Patagonia (dissolved oxygen -DO below 2 mL L -1 ). Hydrographic sampling between 1995-2015 confirmed hypoxia below 100 m depth, down to the bottom (250 m). A line of sensors at an oceanographic mooring in Puyuhuapi were deployed to continuously record the temporal-vertical behaviour of water column temperature and salinity from the surface down to 120 m, from February to July 2015. A Multi-parameter water quality sonde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This study was focused on identifying the potential for mucus‐driven nutrient enrichment in the environment and its effect on natural microbial communities from aquaculture influenced fjord in Northern Patagonia (Buschmann et al, 2006). The conditions in seawater were associated with the estuarine circulation with low salinity waters at the surface (2 m) and marine conditions at deeper water (100 m) as has been previously described in the Puyuhuapi Fjord (Pérez‐Santos et al 2017). The addition of mucus produced by Salmon epithelium triggered changes in nutrient dynamics in the estuarine surface as well as marine waters in a deeper layer.…”
Section: Discussionmentioning
confidence: 72%
“…This study was focused on identifying the potential for mucus‐driven nutrient enrichment in the environment and its effect on natural microbial communities from aquaculture influenced fjord in Northern Patagonia (Buschmann et al, 2006). The conditions in seawater were associated with the estuarine circulation with low salinity waters at the surface (2 m) and marine conditions at deeper water (100 m) as has been previously described in the Puyuhuapi Fjord (Pérez‐Santos et al 2017). The addition of mucus produced by Salmon epithelium triggered changes in nutrient dynamics in the estuarine surface as well as marine waters in a deeper layer.…”
Section: Discussionmentioning
confidence: 72%
“…The carbon export to deeper waters can enhance the action of microbial carbon pump and fuel activity of subsurface heterotrophic microbes which promotes oxygen consumption. Consistently, some authors have proposed that the hypoxia observed in deep waters of Puyuhuapi Fjord could be partially explained by such organic matter respiration (Schneider et al, 2014;Silva and Vargas, 2014;Pérez-Santos, 2017).…”
Section: Heterotrophic Bacterial Activity On Autochthonous Vs Allochthonous Dissolved Organic Mattermentioning
confidence: 71%
“…On the other hand, we also do not include additional sources of organic matter that could exacerbate oxygen depletion, both from salmon farm activity (e.g., mortality, feces) and local coastal populations. We also do not consider hypoxia as a known recurrent condition already in waters of Puyuhuapi Fjord ( Silva and Vargas, 2014 ; Pérez-Santos, 2017 ), a factor that could intensify our estimated impacts of salmon farm organic enrichment.…”
Section: Discussionmentioning
confidence: 99%